Análise cladística de Philodromidae thorell, 1870 (Arachnida: Araneae) - Francisco, Rafael Carlo (Pontifícia Universidade Católica do Rio Grande do Sul, 2015)
Made available in DSpace on 2015-06-12T02:08:16Z (GMT). No. of bitstreams: 1 000470330-Texto+Completo-0.pdf: 14650264 bytes, checksum: e9e557008f28c62060724d7bb7bbf370 (MD5) Previous issue date: 2015 === This work is a cladistic study of Philodromidae Thorell, 1870 at genera level. The family currently have 549 species in 30 genera. Its distribution covers the temperate and tropical regions. Although many authors have studied the family and proposing a systematic classification, no cladistic analysis yet studied the internal relations of the family with a wide sampling of genres. This study aims to analyze the relationship between the genera of Philodromidae and test its monophyly. In the analysis were included 73 species, with representatives of 22 genera of the 30 total family genera and seven species from four families included as outgroups, which were respectively Salticidae, Thomisidae and Sparassidae with two species and representatives for rooting was selected one spiceie of Selenopidae. Where analyzed 130 characters somatic at 80 terminals via heuristic search with equal weighing of characters. The analysis resulted in 61 maximally parsimonious trees of 720 steps, with equal weights. The results at the two analyses have found thath the family is monophyletic. The analysis also indicated three groups of genres that are proposed in this study as subfamilies: Pedinopisthinae, Thanatinae and Philodrominae. Two subfamilies (Thanatinae and Philodrominae) partially match tribes previously proposed in other studies. Many of the diagnostic characters of the show are homoplásicos genres. Cleocnemis and Philodromus shown to be paraphyletic and some monotypic genera were sinonimizados. This result allowed the development of a dichotomous key to genus, which is accompanied by the diagnosis and illustrations of the genera and species used in cladistic analysis. === Este trabalho é um estudo cladístico de Philodromidae Thorell, 1870 ao nível de gênero. A família atualmente agrupa 549 espécies em 30 gêneros. Sua distribuição abrange as regiões temperadas e tropicais. Apesar de vários autores terem estudado a família propondo uma sistemática, nenhuma análise cladistica até o momento estudou as relações internas da família com uma amostragem ampla dos gêneros. O presente trabalho visou analisar as relações entre os gêneros de Philodromidae. Na análise foram incluídas 73 espécies, com representantes de 22 gêneros, dos 30 gêneros da família, e sete espécies de quatro famílias incluídas como grupo externo, sendo elas respectivamente Salticidae, Thomisidae e Sparassidae com duas espécies representantes de cada família. Para o enraizamento foi selecionado uma espécie de Selenopidae. Foram analisados 130 caracteres somáticos em 80 terminais através de busca heurística com pesagem igual dos caracteres. A análise resultou em 61 árvores maximamente parcimoniosas de 720 passos, com pesos iguais dos caracteres. Os resultados recuperam a monofilia da família. A análise também indicou três agrupamentos de gêneros que são propostos neste estudo como subfamílias: Pedinopisthinae, Thanatinae e Philodrominae. Duas subfamílias (Thanatinae e Philodrominae) correspondem parcialmente a tribos propostas anteriormente por outros autores. Muitos dos caracteres diagnósticos dos gêneros demonstram serem homoplásicos. Cleocnemis e Philodromus demonstram ser parafiléticos e alguns gêneros monotípicos foram sinonimizados. Este resultado permitiu a elaboração de uma chave dicotômica ao nível de gênero, que é acompanhada da diagnose e ilustrações dos gêneros e das espécies que foram utilizadas na análise cladística.